2021
DOI: 10.3389/fspor.2021.730151
|View full text |Cite
|
Sign up to set email alerts
|

The Incompatibility of Motherhood and Professional Women's Football in England

Abstract: There has been an advancement of professionalisation of women's football globally. Professional women's football in England has grown exponentially since the inception of the Football Association (FA) Women's Super League in 2011. This article offers an examination of the gender-specific needs of women as professional footballers, focusing specifically on the distinctive aspect of maternity policy. Sportswomen often feel compelled to make the difficult decision between motherhood and an athletic career. Contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
(101 reference statements)
1
6
0
3
Order By: Relevance
“…For instance, qualitative research with competitive recreational athlete mothers described the various cultural (e.g., the cultural norm that a “good” mother prioritizes her child over herself), personal (e.g., attempting to balance motherhood, work and sport with a limited amount of time), and social (e.g., childcare, emotional support to engage in sport) barriers that impact sport participation [ 11 ]. Similar findings have been noted in research that has documented the in-depth experiences of elite athletes who returned to elite-level sport following childbirth [ 1 , 3 , 12 16 ]. In their research with elite distance runners, Appleby and Fisher [ 14 ] described how athletes who returned to competition after pregnancy experienced a transformative process in which they negotiated social stereotypes related to motherhood alongside their athletic identities [ 14 ].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…For instance, qualitative research with competitive recreational athlete mothers described the various cultural (e.g., the cultural norm that a “good” mother prioritizes her child over herself), personal (e.g., attempting to balance motherhood, work and sport with a limited amount of time), and social (e.g., childcare, emotional support to engage in sport) barriers that impact sport participation [ 11 ]. Similar findings have been noted in research that has documented the in-depth experiences of elite athletes who returned to elite-level sport following childbirth [ 1 , 3 , 12 16 ]. In their research with elite distance runners, Appleby and Fisher [ 14 ] described how athletes who returned to competition after pregnancy experienced a transformative process in which they negotiated social stereotypes related to motherhood alongside their athletic identities [ 14 ].…”
Section: Introductionsupporting
confidence: 85%
“…The athletes in our study echoed both the challenges and joy of becoming a mother but also identified key strategies that sporting organizations, coaches and athletes can take to reduce these barriers and facilitate the retention of mothers in elite sport. Clear maternity and family policies are often missing from sport policy [ 4 , 16 ]. Athletes highlighted the urgent need to develop policies that do not penalize athletes for taking a parental leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os estudos que tinham como desenho metodológico alguma intervenção direta com as atletas, principalmente, no uso de entrevistas e aplicação de instrumentos de avaliação, incluíram atletas que estavam em uma gestação ou que tiveram pelo menos um filho durante sua carreira (FORSTMANN, et al, 2022;DIETZ, et al, 2022;DAVENPORT et al, 2022;MASSEY;WHITEHEAD, 2022;DAVENPORT et al, 2023;CULVIN;BOWES, 2021;TEKAVC;WYLLEMAN;ERPIČ, 2020;DARROCH et al, 2019;SUNDGOT-BORGEN et al, , 2019). A maioria dos estudos que realizaram entrevistas com as atletas apresentou a média de idade das participantes.…”
Section: Bmcunclassified
“…Сучасний спосіб життя диктує зміни у фізичній активності чоловіків і жінок, яка набуває гіпертрофованих форм при заняттях професійним спортом. Тому дуже важливим є питання врахування і вивчення як позитивного, так і негативного впливу різних чинників на репродуктивну функцію людини, зокрема жінок репродуктивного віку, які займаються професійним спортом [1][2][3][4][5][6][7].…”
Section: вступunclassified